Efeitos da suplementação com carboidrato e glutamina sobre a resposta imunológica inata, inflamação, estresse oxidativo e dano tecidual no cérebro após exercício na hipóxia - Caris, Aline Venticinque [UNIFESP] (2017)
INTRODUCTION: It is known that exercise can be immunomodulatory, stimulating or inhibiting the immune response. Hypoxia has been described as a potent immunosuppressive agent. Hypoxia increases oxidative stress, inflammation and CNS damage; and strenuous exercise may exacerbate the effects of hypoxia. On the other hand, recent evidence suggests that carbohydrate and glutamine supplementation may attenuate the effects of exercise realized on hypoxia. Thus, this study intends to evaluate the effects of carbohydrate and glutamine supplementation on parameters of innate immune response, inflammation, oxidative stress and tissue damage in the brain after exercise in hypoxia. MATERIAL AND METHOD: Fifteen physically active men underwent three exercise sessions until exhaustion with intensity of 70% VO2peak in a normobaric chamber (Colorado Altitude Training / 12 CAT-Air Unit) simulating 4,500 m altitude, as follows: (1) Exercise in hypoxia+placebo; (2) Exercise in hypoxia+CHO (8% maltodextrin - 200mL / 20min) and (3) Exercise in hypoxia+GLN (6 days of supplementation with glutamine (20g / day) and carbohydrate (8% maltodextrin-200mL / 20min) during the exercise and for 2h of recovery. All procedures were double blind and randomized. The concentration of plasma, salivary and cytokine by monocytes parameters were evaluated before entering the chamber (basal), after 2h of rest (pre-exercise), immediately after exercise (post-exercise) and after 2h of recovery remaining in the chamber. After a normality test, ANOVA for repeated measures was performed followed by Tukey's post-test, considering significance level of p < 0.05. RESULTS: There was a reduction in the SaO2% after 2 h of exposure to hypoxia (p <0.001) for all conditions, and at the pre-exercise vs post-exercise moment (p <0.001) in the hypoxia condition. However, after 2h of recovery the SaO2% was partially restored in the two supplemented conditions (p <0.001). Hypoxia and exercise worsened the ability of monocytes to respond to LPS, increased glucose concentration (p = 0.01), Cortisol (p = 0.01), IL-6 (p <0.001), S100β (p <0.001), EPO (p = 0.01) and decreased glutamine level (p = 0.01). These changes were partially reversed by carbohydrate and glutamine supplementation, respectively, by elevation of IL-10 (p <0.01) and reduction of IL-1β (p = 0.02) and TNF-α (p = 0.02). CONCLUSION: The present study observed that monocytes were not able to respond to LPS after exposure to hypoxia and exercise, as such condition increased BBB permeability, but it was not sufficient to promote alteration in salivary IgA. However, the GLN supplementation stimulated the anti-inflammatory action, reducing the production of pro-inflammatory cytokines. On the other hand, supplementation with CHO and discreetly with GLN, promoted changes in the pro / anti -inflammatory balance stimulating an anti-inflammatory response in the oral mucosa.